Taiwan Government-Guided Strategies Contributed to Combating and Controlling COVID-19 Pandemic - Chen, Chung-Chu; Tseng, Cheng-Yin; Choi, Wai-Mau; Lee, Ya-Chun; Su, Tsung-Hsien; Hsieh, Chin-Yi; Chang, Chih-Ming; Weng, Shun-Long; Liu, Po-Huang; Tai, Yu-Lin; Lin, Chien-Yu (Frontiers in Public Health, 2020)
Coronavirus disease 19 (COVID-19) is highly contagious and an emerging health crisis worldwide. The optimal strategies to prevent disease spread is inconclusive and the adopted measurements combating COVID-19 varied in different countries. Taiwan is geographically close to China and at high risk of disease spread. We conducted this study to investigate the incidences of COVID-19 and Taiwan’s strategies. We collected the epidemiological data of COVID-19 in some countries and Taiwan had a successful story to combat the pandemic. As of middle March 2020, we performed internet search to collected related information, including the website of world health organization (WHO) and other websites. Furthermore, we reviewed the government-guided strategies and our hospital measurements in Taiwan. Authentic photos are provided to demonstrate the practical situations. As of middle March, Taiwan had high rates of performed diagnostic tests (688.5 tests per million citizens) and a lower infected rate (49 cases, 2.1 cases per million people). We summarized some important strategies to combat COVID-19, including (1) border control, (2) official media channel and press conference, (3) name-based rationing system for mask, (4) TOCC-based rapid triage, outdoor clinics and protective sampling device, and (5) social distancing, delay of new semester and restriction of religious assembly. In conclusion, Taiwan had lower rates of COVID-19 and Taiwan government-guided strategies contributed to controlling disease spread.